The natural history, sensory ecology and biogeography of the seed dispersal of large fruits in Fynbos - White, Joseph D M (Department of Biological Sciences, 2019)
Seed dispersal is a crucial life-history stage for the regeneration of all reseeding plants. In the Fynbos Biome of the Greater Cape Floristic Region (GCFR) of South Africa, at least 100 plant species have seed traits that suggest they are scatterhoarded by small mammals. The aims of this thesis were to investigate the dispersal biology of large-fruited Fynbos plants by: 1) determining the spatial and taxonomic extent of scatter-hoarding through seed trials, investigating both dry, nut-like and semi-fleshy fruits; 2) trait-based analyses investigating selective drivers of seed colour polymorphisms in flat-winged, serotinous Leucadendron and 3) modeling the relative influence of environmental, biological and disturbance drivers in predicting the distributions of serotinous and scatterhoarded Leucadendron. Seed predation and scatter-hoarding by small mammals was widespread, yet locally patchy. Four new fynbos species with large, nut-like fruits were confirmed to be scatter-hoarded, by either Acomys subspinosus or Gerbilliscus paeba. Many species with small, nut-like fruits, with no clear dispersal or defense strategies, suffered intense seed predation by the nonhoarding small mammals, Rhabdomys pumilio and Micaelamys namaquensis. The large, dry, nut-like fruits of Ceratocaryum argenteum have a globally unique, alternative strategy for effective dispersal. The nuts emit a strong scent that mimics the scent of herbivore dung and exploits the olfactory sensory perception of dung beetles, which rolled and buried the seeds. The semi-fleshy fruits of the rock-restricted Heeria argentea were dispersed by the mutualistic M. namaquensis, which consumed only the pericarp, allowing for germination, as well as moving fruits to fire-protected, rocky outcrops. Many flat-winged Leucadendron seeds, with polymorphic brown or black seed coats, displayed background matching with post-fire soils. This plant defense likely reduces predation by visually cued avian granivores. Finally, modeling results suggest that the distributions of both serotinous and scatter-hoarded plants are strongly negatively and positively influenced by more intense seasonal drought and longer fire return interval in the GCFR, respectively. Overall, this thesis advances our understanding of large-fruited Fynbos plants, providing unique insights into their natural history, ecology, evolution, conservation and biogeography.